A visualization of the Jacobsthal sequence with the contribution of GeoGebra: Uma visilização da sequê de Jacobsthal com o aporte do GeoGebra - Souza Rodrigues Pinheiro, Carla Patrícia (2023)
In Brazil, according to research, there are few works on the Jacobsthal sequence in undergraduate courses, and this motivated this work, given the intriguing particularity of its definition. Therefore, the objective of this work is to investigate a didactic proposal that enables the understanding of the Jacobsthal sequence through a geometric visualization supported by the GeoGebra software. For its structuring, the methodology used was Didactic Engineering, in its first two phases – preliminary analysis and a priori analysis – with the perspective of the Theory of Didactic Situations, which is a theory of teaching. As a result, we have two-dimensional and three-dimensional visualization, from the construction of tiles and prisms relating to the Jacobsthal numbers.